Implementasi CUK Inverting Konverter Pada Battery Charging Terintegrasi Fotovoltaik Berbasis PID - Amalia, Rahma Nur; Syamsiana, Ika Noer; Madani, Lingga Ahadian; Widhi, Tri Warisaning (Politeknik Negeri Malang, 2025)
This study aims to test the performance of PWM, voltage sensors, ACS712 current sensors, and the efficiency of the inverting CUK converter in an energy conversion system. PWM testing showed a stable output frequency of 31.250 Hz across various duty cycles. Voltage sensor testing resulted in an average error of 1.2% for the solar panel sensor and 2.2% for the battery sensor, indicating good accuracy. ACS712 current sensor testing showed an average error of 1.5% at the solar panel input and 9.7% at the converter output to the battery. The inverting CUK converter achieved a maximum efficiency of 89% at a 14% duty cycle. These results indicate that the developed system has high accuracy and efficiency in power conversion. Paying attention to efficiency and accuracy will bring great benefits, such as cost efficiency, system stability, high energy quality. An important contribution of this research is to improve the efficiency and stability of renewable energy systems, especially those integrated with solar panels and batteries, and to support the development of more environmentally friendly and sustainable energy solutions.